Antibiotic therapy in autoimmune disorders. (January 2014) - Rosman, Yossi; Lidar, Merav; Shoenfeld, Yehuda
SUMMARY:  Antibiotics have been applied for the treatment of autoimmune diseases for over five decades, based on the premise that infections play a role in the initiation and propagation of these entities. The mechanisms by which an infection may trigger an autoimmune reaction include the so-called 'molecular mimicry', 'epitope spreading' or 'bystander activation'. The association between infection and autoimmunity may be directly evident, as in cases of reactive arthritis, or in a more roundabout manner, as exemplified by the association between anaerobic bacterial infection of the gums and rheumatoid arthritis. Moreover, some antibiotics have, in addition to their antibacterial effects, anti-inflammatory and immunomodulatory properties. In this review we focus on the rationale and possible benefits of antibiotic treatment in various autoimmune diseases, including rheumatoid arthritis, reactive arthritis, granulomatosis with polyangitis, immune thrombocytopenia purpura and the antiphospholipid syndrome.